HAKIKAT SENI DALAM PEMIKIRAN SUDJOJONO DAN RELEVANSINYA DENGAN SENI RUPA KONTEMPORER DI INDONESIA - , anastasia jessica adinda susanti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The essence of art is an endless debate. Sudjojono, Indonesian thinkers of art and painters in 1930s era, assert that the nature of art is an expression of the artist that can be seen or called Jiwa Ketok. The essence of art in Sudjojonoâs thought important to be researched because of differences opinion and conflicts in Sudjojonoâs concept of art, so that the essence of art in Sudjojonoâs thought need to be explored in order to obtain a clearer and whole understanding. Aim of the research is to examine the concepts of art, essensce of art in Sudjojono thinking, contradictions and relevance of Sudjojonoâs ideas with contemporary Indonesian fine arts. This research is literature research with Sudjojonoâs ideas as material objects and philosophy of art as a formal object. This research uses traditional philosophy of art approach through descriptive theory that completed with normative and sociological theory. Method that used in this research is hermeneutic method with methodical elements: description, interpretation, internal coherence, historical continuity, and heuristics. Analytical framework that used is the value of art, form and expression of art, artists and art context. The results of this research point out that the essence of art according Sudjojono is Jiwa Ketok or in other words, manifestation of expression of the soul. Contradictions found in Sudjojonoâs thinking that related to form and expression of art is conflict between artistic credo Jiwa Ketok with realism that recommended by Sudjojono and Sudjojono themselves are not always faithful to realism. Sudjojono often paint in expressionist approach. Another contradiction is related to the value of art is Sudjojono believe that art is objective but history shows that prolonged disagreements about the valuation of the arts happen. Another contradiction is in duty of artist that is Sudjojono suggest freedom in painting and yet on the other hand Sudjojono suggest a theme that needs to be raised in the painting is that the painting departed from the reality. Sudjojonoâs thought although having some contradictions in it but it is an important as starting point for philosophy of art discourse in Indonesia. Relevance of Sudjojonoâs thought with Indonesian contemporary fine arts can be recognized from the concept of Jiwa Ketok as a principle in the creation of the work